Tantangan dan Peluang Pendidikan Islam dalam Konteks Modern - Harahap, Sofiah; Pohan, Nur Jannah; G, Gusmaneli (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Islamic education today faces a complex epistemological dilemma, caught between the sacred force of normative tradition and the progressive tide of modernity. Amid the rapid advancement of information technology, cultural globalization, and the shift toward more transformative and student-centered pedagogical paradigms, Islamic education confronts contemporary challenges such as value secularization, a crisis of religious identity among learners, and the dominance of profane scientific narratives often misaligned with the values of tawhid. This study critically explores these dynamics through a qualitative approach using literature review and reflective analysis of socio-religious realities. The findings reveal that, despite the magnitude of these challenges, strategic opportunities exist for Islamic education to reposition itself—both theoretically and practically—through the integration of classical Islamic knowledge with modern scientific approaches. The utilization of digital technologies for da’wah and adaptive learning, the application of liberating critical pedagogy, and the revitalization of spiritual values and prophetic ethics emerge as key responses to the complexities of the post-truth and postmodern era. Nevertheless, internal barriers such as curriculum stagnation, conservative institutional culture, and a lack of methodological innovation among Islamic educators remain critical issues. Therefore, this article recommends a reformulation of Islamic educational paradigms based on tawhidic values, integral humanism, and liberation pedagogy as the foundation for building an Islamic civilization that is not only adaptive but also proactive in shaping the future of humanity.